(untitled) (REMUNOM, 2024)
The Multiprofessional Residencies in the Health area (RMS) were created with the aim of consolidating the learning principles linked to professional practice and theorization, with concepts of critical reflection, revealing effective actions and services to train and qualify the human resources that will act in the country’s Public Health Policy, as a lato sensu postgraduate teaching modality and developed on an exclusive dedication basis with teaching-care supervision under joint responsibility of the health and education sectors. This article aimed to analyze residents’ perception of the academic preceptorship activity of the Uniprofessional and Multiprofessional Residency Programs of a university hospital located in the western region of Paraná-PR. The residents’ main notes were related to theoretical and practical activities; the physical structure and available materials/resources; the in-service training hours; the actions developed by residents, preceptors and tutors; the motivation to attend residency programs; the in-service training scenario; and suggestions for adjustments to residency programs. Other studies can be carried out, with regard to the evaluation of residency, preceptorship and tutoring, seeking to identify the developments and repercussions generated in the hospital, in addition to the impact of training preceptors in the teaching-learning process in the residency.